2016
DOI: 10.1097/tp.0000000000001066
|View full text |Cite
|
Sign up to set email alerts
|

Viral Origin, Clinical Course, and Renal Outcomes in Patients With BK Virus Infection After Living-Donor Renal Transplantation

Abstract: Pretransplant urinary BKV shedding of donor and recipient is a risk for posttransplant infection. Donor-derived BKV transmission is an important mode of infection. BKV subtype IV may be one of the viral determinants. Early BKV positivity of urine and blood indicates later BKV nephropathy. Decreased renal function may favor BKV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
60
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 42 publications
8
60
2
Order By: Relevance
“…In the viremia group genotype IV was more prevalent after genotype I. This outcome differs from the one recently published by Schwarz et al where genotype IV was more prevalent in the BKPyVAN group [32]. This discrepancy could possibly be explained to the different distribution of BKPyV genotypes in the population throughout the world, as described by others [3335].…”
Section: Discussioncontrasting
confidence: 61%
“…In the viremia group genotype IV was more prevalent after genotype I. This outcome differs from the one recently published by Schwarz et al where genotype IV was more prevalent in the BKPyVAN group [32]. This discrepancy could possibly be explained to the different distribution of BKPyV genotypes in the population throughout the world, as described by others [3335].…”
Section: Discussioncontrasting
confidence: 61%
“…A German study comparing 20 donor recipient pairs through VP1 typing region also concluded that the virus shed by recipients most likely come from the donor . And, more recently, Schwarz et al also demonstrated the donor‐origin of the virus in 24 of 28 living donor‐recipient pairs.…”
Section: Discussionmentioning
confidence: 72%
“…In addition to potent immunosuppression, risk factors for BKVAN after KTx include treatment for allograft rejection, ureteral stent indwelling time, and pretransplantation donor‐recipient pair seroreactivity . These reports have raised awareness that BK infection after KTx could be from reactivation of recipient's BKV or donor‐derived transmission . A better understanding of the epidemiology of BKV genotypes among KTx recipients may advance future studies to prevent BKVAN or to help develop a vaccine for BK virus among KTx recipients …”
Section: Introductionmentioning
confidence: 99%